A new methanation and membrane based power-to-gas process for the direct integration of raw biogas – Feasability and comparison. (1st March 2018) - Kirchbacher, Florian; Biegger, Philipp; Miltner, Martin; Lehner, Markus; Harasek, Michael
Abstract: Storage options for increasing amounts of volatile energy supplied by renewable sources are of growing interest. One promising concept is power-to-gas, where electrical energy is transformed to gas that can be stored more easily. H2 produced by electrolysis powered by excess energy is combined with CO2 in a methanation to produce CH4 . Possible CO2 sources are numerous, but biogas is special, as it is a renewable source itself and already contains CH4 concentrations of up to 60% v/v. Normally the CH4 needs to be removed prior to methanation, requiring two gas upgrading steps. The newly developed process described in this paper circumvents this by directly feeding biogas to the methanation. For evaluation of this concept two process chains were realized. The classic setup consisted of a catalytic methanation and membrane based gas upgrading being fed with H2 and CO2 from bottles. The alternative process was coupled with a two-stage fermentation to study effects of changing biogas compositions. Both process chains have been demonstrated on a scale of about 0.5 m 3 (STP)/h. Results for both will be presented in this work and the positive implications regarding the future implementation of biogas into power-to-gas systems will be discussed. Highlights: Combination of methanation and membrane based gas upgrading. Demonstration plant for the integration of biogas into power-to-gas systems realized. Effects of pressure and GHSV dependency shown. Quality for gas grid injection was reached for the produced SNG (>96% v/v CH4 ).